Microaggressions and Modern Racism Endurance and Evolution - Levchak, Charisse C. (Springer International Publishing, 2018)
Microaggressions and Modern Racism: Endurance and Evolution explores the causes, manifestations, and consequences of microaggressions, macroaggressions, and modern racism within society. Using surveys and interview data alongside examples in mainstream media, Levchak provides a comprehensive analysis of modern racism on college campuses, in workplaces, and in various media. In so doing, she expands microaggression theory and explores race-based aggression and race relations through sociological and social justice frameworks. The resources offered here have the potential to inform anti-racism policy, programming, and practice that can impact the lives and well-being of all people.